KAJIAN PENERAPAN TEORI PEMBELAJARAN BERMAKNA AUSUBEL BERDASARKAN PERSPEKTIF ALKITABIAH PADA MATERI HIDROKARBON [A STUDY ON THE APPLICATION OF AUSUBEL'S MEANINGFUL LEARNING THEORY ON HYDROCARBON CHEMICAL LEARNING BASED ON A BIBLICAL PERSPECTIVE] - Sekar Kinasih; Kelly Sinaga (Universitas Pelita Harapan, 2020)
Learning about hydrocarbons in a chemistry class requires a high understanding of concepts and memory. Students usually only focus on memorizing and understanding the material when studying hydrocarbons in order to get good grades during exams, as happened to the grade 11 students in one of the schools in Lampung. This results in students not really learning about hydrocarbons and how they are useful for daily life. The purpose of writing this paper is to explain the study of the application of Ausubel's meaningful learning theory with the Contextual Teaching and Learning (CTL) strategy on hydrocarbon material based on a biblical perspective. Ausubel's meaningful learning theory with a Contextual Teaching and Learning strategy can help students find the meaning of learning because this theory emphasizes the integration of information that is relevant to a student's life or context. Through contextual learning students also obtain life values based on a biblical perspective. The method of writing this research is a literature study based on 20 reference sources. The conclusion obtained is that each stage in Ausubel's meaningful learning theory with a contextual approach can help students find the meaning of learning by connecting old knowledge with new knowledge that is more relevant to life. Students can also add value to their life by becoming wise users of petroleum which is a hydrocarbon.BAHASA INDONESIA ABSTRACT: Hidrokarbon adalah salah satu materi pembelajaran kimia yang membutuhkan pemahaman konsep dan daya ingat yang tinggi. Siswa biasanya hanya fokus menghafalkan dan memahami materi ketika belajar hidrokarbon agar bisa memperoleh nilai yang baik saat ujian, seperti yang terjadi pada siswa kelas XI SMA di salah satu sekolah di Lampung. Hal tersebut mengakibatkan siswa tidak menemukan makna dalam pembelajaran hidrokarbon yang berguna bagi kehidupan sehari-hari. Tujuan penulisan makalah ini adalah untuk memaparkan setiap tahapan dalam penerapan teori pembelajaran bermakna Ausubel dengan strategi Contextual Teaching and Learning (CTL) pada materi hidrokarbon berdasarkan perspektif Alkitabiah yang dapat menolong siswa menemukan makna pembelajaran yang relevan dengan kehidupan siswa atau kontekstual. Melalui pembelajaran yang kontekstual siswa juga memperoleh nilai-nilai kehidupan berdasarkan perspektif Alkitabiah. Metode penulisan penelitian ini adalah kajian literatur berdasarkan 20 sumber referensi. Kesimpulan yang diperoleh yaitu setiap tahapan dalam teori pembelajaran bermakna Ausubel dengan pendekatan kontekstual dapat menolong siswa menemukan makna belajar melalui menghubungkan pengetahuan lama dengan pengetahuan baru yang lebih relevan dengan kehidupan. Siswa juga dapat memperoleh nilai kehidupan untuk menjadi pribadi yang berhikmat dan bijaksana dalam menggunakan minyak bumi.